Isolation and Characterization of Cellulose-decomposing Bacteria Inhabiting Sawdust and Coffee Residue Composts - Eida, Mohamed Fathallh (Japanese Society of Microbial Ecology/The Japanese Society of Soil Microbiology, 2012)
Clarifying the identity and enzymatic activities of microorganisms associated with the decomposition of organic materials is expected to contribute to the evaluation and improvement of composting processes. In this study, we examined the cellulolytic and hemicellulolytic abilities of bacteria isolated from sawdust compost (SDC) and coffee residue compost (CRC). Cellulolytic bacteria were isolated using Dubos mineral salt agar containing azurine cross-linked (AZCL) HE-cellulose. Bacterial identification was performed based on the sequence analysis of 16S rRNA genes, and cellulase, xylanase, β-glucanase, mannanase, and protease activities were characterized using insoluble AZCL-linked substrates. Eleven isolates were obtained from SDC and 10 isolates from CRC. DNA analysis indicated that the isolates from SDC and CRC belonged to the genera Streptomyces, Microbispora, and Paenibacillus, and the genera Streptomyces, Microbispora, and Cohnella, respectively. Microbispora was the most dominant genus in both compost types. All isolates, with the exception of two isolates lacking mannanase activity, showed cellulase, xylanase, β-glucanase, and mannanase activities. Based on enzyme activities expressed as the ratio of hydrolysis zone diameter to colony diameter, it was suggested that the species of Microbispora (SDCB8, SDCB9) and Paenibacillus (SDCB10, SDCB11) in SDC and Microbispora (CRCB2, CRCB6) and Cohnella (CRCB9, CRCB10) in CRC contribute to efficient cellulolytic and hemicellulolytic processes during composting.